KANDUNGAN NITROGEN BEBERAPA JENIS TANAMAN PUPUK HIJAU PADA TANAH MASAM YANG DIAPLIKASI KAPUR - Siti Zahrah (Jurnal Sagu, 2010)
This research was comiucted in Green House and Soil Laboratory, Andalas Univeraity, Padang. Theresearch aimed to study the efTect oflimiag in acid soil (Ultisol) to nitrogen content of green mannrecrops.The experiment used Completely Randomaed Design of factorial 7x 2. Tbe first factor was f^enmanure crops, consisted of seven levels (CalioHibn tetragma, Flemingia coHgefta, GKriddia stpmm,Leucaena leucocepkala, Leucaena gktttca, Seshania rostrata, SesbaHta seshoK) and second factor was limeaddition, consisted of two levels ( without liming and IxAi-dd). The result of research for four times cattingsindicated that: (1) The highest total N without liming was Fkmuigiaa>i^esta (1225,96 mg/pot), and Leacaenaleueocepkala (2729,53 mg/pot) in acid soil with liming It Al-dd; (2) Tbe highest increasing percenUges oftotal N as responses to liming were Cailandra taragona (67,48%), LeHcaena leucocqtkala (61,29%),Gliricidm sepium (57,75%), Sesbaida sesbim (44,60%), [Micaena glauca (43,44%), and Flemingia etmgesta(18,83%); (3) Flemingia congesta was very tolerant to acid so9 and (Miandratetrvgomt was very responsiveto liming.